PERAN SULTAN ISKANDAR MUDA DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI NUSANTARA MASA KESULTANAN ACEH DARUSSALAM TAHUN 1607 – 1636 - Ilham Maulana; M kautsar Thariq; Samsudin Samsudin; Yan Nurcahya (Sekolah Tinggi Agama Islam Al-Andina, 2024)
Abstract : The progress of Islamic development and civilization in the archipelago was marked by the establishment of Islamic sultanates, one of which was Aceh Darussalam. This sultanate reached the peak of its glory and also became the center for the development of Islam in various regions of the archipelago in the 17th century AD during the time of Sultan Iskandar Muda. The aim of this research is to explore the role and political policies implemented during the reign of Sultan Iskandar Muda in the process of developing and expanding Islamic da'wah. This research uses library study methods from various sources such as books, journals, magazines and other documents. The results of this research are that the Sultanate of Aceh Darussalam since its founding until it experienced the peak of progress, especially during the time of Sultan Iskandar Muda, who paid great attention to the development of Islam, has influenced the process of developing and spreading Islamic da'wah in the archipelago, one very important factor is the enactment of qanun meukata alam as State law and Islam received support and legitimacy from the authorities in Haramayn (Mecca and Medina), Islamic teaching centers were developed through institutions that gave birth to Muslim educational scholars who had an influence on that period by producing intellectual works that are still used as references today. This research is important to be used as a reference and additional insight for the development of historical science, especially in exploring insights between the role of Islamic sultanates in the development of Islam in the archipelago. Keywords : Aceh Darussalam, Iskandar Muda, Nusantara, Islamic Development, Ulama